The grain growth in alumina compacts sintered under high pressure - Ozturk, Zeynep Taslicukur; Kuskonmaz, Nilgun (WALTER DE GRUYTER GMBH, 2018)
In this study, alumina ceramics were produced with high density and nanograin size without additives from nano-size gamma-Al2O3. The effects of sintering pressure (3 GPa and 7 GPa) and temperature (600 degrees C and 1 200 degrees C) on the grain size of sintered samples were studied. It was shown that high pressure increases the nucleation rate while reducing the growth rate of the transformed alpha phase. Pressure-assisted densification decreases grain size, so that nano-scale grains can be achieved in the sintered structure. The effect of various sintering conditions on grain growth in alumina was investigated during high-pressure sintering for better understanding of pressure and temperature effects on microstructural properties.
Keywords: Al2O3; Sintering; Grain growth; TEMPERATURE; CERAMICS; Metallurgy & Metallurgical Engineering